Assessing Cost of Quality in a Medical Device Division of a Training Hospital: A Case Study in Iran - Reza Jabarbeigi; Roohollah Kalhor; Sima Rafiei; Fariba Hashemi (Shahid Sadoughi University of Medical Sciences, 2021)
Background: Cost of Quality is an approach that helps organizations evaluate the extent to which their resources are used to prevent poor quality activities, assess the quality of provided services, or evaluate the number of resources that are wasted due to the internal and external failures occurring in a system. The research objective was to measure the Cost of Quality(CoQ) in a medical device division of a hospital in Qazvin, Iran. Methods: We performed a qualitative study in the medical device division in a public hospital affiliated with Qazvin University of Medical Sciences, Iran in 2020. To measure and report the (CoQ) in the division, the Prevention-Appraisal-Failure (PAF) model was used. Data were collected through document review, semi-structured interview, and group discussion, which were entered into the Excel software to calculate their distribution and frequencies using the descriptive statistics method. Results: Among different cost categories, the highest amount of expenditures belonged to internal and external failure costs. Results also revealed that several factors were responsible for the failures, including lack of knowledge of personnel about the proper use of medical devices; failure to periodically perform calibration on due dates; lack of adequate supervision; stress and work pressure among employees; and lack of managerial commitment toward the importance of preventive maintenance. Conclusion: In order to decrease the number of failures occurring in a working system, it is required to increase personnelchr('39')s knowledge about the proper use of medical devices, perform calibration of devices on due dates, increase managerial commitment toward preventive and quality appraisal activities and apply systematic supervision.